2019
DOI: 10.1088/1748-9326/ab2da8
|View full text |Cite
|
Sign up to set email alerts
|

Are e-scooters polluters? The environmental impacts of shared dockless electric scooters

Abstract: Shared stand-up electric scooters are now offered in many cities as an option for short-term rental, and marketed for short-distance travel. Using life cycle assessment, we quantify the total environmental impacts of this mobility option associated with global warming, acidification, eutrophication, and respiratory impacts. We find that environmental burdens associated with charging the e-scooter are small relative to materials and manufacturing burdens of the e-scooters and the impacts associated with transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 296 publications
(256 citation statements)
references
References 22 publications
7
246
1
2
Order By: Relevance
“…For the manufacturing phase, due to lack of data from the Chinese factory, we followed the recommendations from Hollingsworth et al [16] and used the manufacturing of an electric bicycle (proportional to its weight) as proxy data. The transport phase was modeled based on the data from the provider, the e-scooter being transported by lorry from the factory to Shenzhen, then shipped from Shenzhen harbor to Rotterdam's harbor and, finally, by lorry from Rotterdam to Brussels.…”
Section: Inventory Data For the E-scootermentioning
confidence: 99%
See 4 more Smart Citations
“…For the manufacturing phase, due to lack of data from the Chinese factory, we followed the recommendations from Hollingsworth et al [16] and used the manufacturing of an electric bicycle (proportional to its weight) as proxy data. The transport phase was modeled based on the data from the provider, the e-scooter being transported by lorry from the factory to Shenzhen, then shipped from Shenzhen harbor to Rotterdam's harbor and, finally, by lorry from Rotterdam to Brussels.…”
Section: Inventory Data For the E-scootermentioning
confidence: 99%
“…In order to compare our PSS case study to the ownership model we have modeled another e-scooter which can be found on the market. We modeled it based on the inventory given in the appendices in Hollingsworth et al [41] who disassembled and inventoried all the materials of the different components. As the owner of an e-scooter charge it at home, no distribution phase is included in this model.…”
Section: Inventory Data For the Personal E-scootermentioning
confidence: 99%
See 3 more Smart Citations